Spleen elegy - Labbe, Jason (BlazeVOX [books], 2017)
Let’s twin and twine together two primary aspects of how America can see herself—the good atoms of Whitman’s leaves of grass, and the engines humming their freedom on the highways that cut across those 19th century fields. Now, Jason Labbe well knows, as Whitman’s atoms become pixels, we find ourselves at a crossroads, learning again and again the consequences of “the indescribable way you shape / a past of little use.” Seeking to find that law or logic to shattering, be it in the memory-echo of personal trauma caught on infinite loop in the mind, or be it the dismal virtualities of the post-modern ether, the poems of Spleen Elegy unfold their rueful nostalgia: “I have something accurate to say that lacks perspective.” That may well be the very accuracy we most need, riding the routes of America, the byways and frontage roads, seeking anyone who is willing for a poem or two to see. —Dan Beachy-Quick "A chunk of broken tar”—that's the color of this book. And the sound of this book is "a train in the static." Its poems count time in "decaseconds of dusk." To read this book is to feel the uneasy passivity and unerring stuckness, the particular absurdity, of certain citizens stuck in this millennium. So many lines made me laugh. And sigh. But not cry. Jason Labbe is great at melancholy. Baudelaire's mosquito is definitely here: "I am Past / who passing lit and sucked your life and left." The future is unthinkable and unalterable. Except. Except! Lucretius' swerve is also here. Atoms may veer randomly, which is extra significant in a book that takes place mostly on the road. "My sutures are beautiful as a tread pattern," he says, and it is easy (and dangerous) to fall in love with Labbe's strangled version of optimism. —Darcie Dennigan
Keywords: dept.eng

Maps for Jackie - Labbe, Jason (BlazeVOX Books, 2020)
"Poetry's natural habitat is one of detail, radiant or tarnished, an intimate geography that draws us close to where presence is an act of perception: world into word. In Maps for Jackie, Jason Labbe navigates a terrain of singular encounters and incidents, tactile, luminous and animated by the sensuous abrasions and comforts of the heartmind as they touch down on his, and our, present: white leaf is like a moth / wing I'd fix to her shoulder.--Ann Lauterbach"--The back cover
Keywords: 21st century; American poetry; dept.eng; faculty_collection